2009
DOI: 10.5194/angeo-27-4239-2009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between variability of the semidiurnal tide in the Northern Hemisphere mesosphere and quasi-stationary planetary waves throughout the global middle atmosphere

Abstract: Abstract. To investigate possible couplings between planetary waves and the semidiurnal tide (SDT), this work examines the statistical correlations between the SDT amplitudes observed in the Northern Hemisphere (NH) mesosphere and stationary planetary wave (SPW) with wavenumber S=1 (SPW1) amplitudes throughout the global stratosphere and mesosphere. The latter are derived from the Aura-MLS temperature measurements. During NH summerfall (July-October), the mesospheric SDT amplitudes observed at Svalbard (78 • N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
5
19
0
Order By: Relevance
“…10), in particular the NMT s = +1 (related to SPW S = 1) in the southern summer. This feature has also been observed, as noted in the Introduction (Paper 1; Hibbins et al, 2010;Xu et al, 2009a, c;Murphy et al, 2009;Baumgaertner et al, 2005Baumgaertner et al, , 2006. These 3 groups of authors also demonstrate that there are significant correlations and probable causal linkages between the SPW S = 1 of the NH-winter and both the directly observed winter-SDT and the related NMT s = +1 of the SHsummer.…”
Section: Plots Of Monthly Mesospheric Mt and Nmt Preferences (2006-20supporting
confidence: 53%
See 2 more Smart Citations
“…10), in particular the NMT s = +1 (related to SPW S = 1) in the southern summer. This feature has also been observed, as noted in the Introduction (Paper 1; Hibbins et al, 2010;Xu et al, 2009a, c;Murphy et al, 2009;Baumgaertner et al, 2005Baumgaertner et al, , 2006. These 3 groups of authors also demonstrate that there are significant correlations and probable causal linkages between the SPW S = 1 of the NH-winter and both the directly observed winter-SDT and the related NMT s = +1 of the SHsummer.…”
Section: Plots Of Monthly Mesospheric Mt and Nmt Preferences (2006-20supporting
confidence: 53%
“…(Manson et al, 2004a and b;Forbes et al, 2003;Cierpik et al, 2003). It is therefore possible for radars to have been located, by the chances provided for available land, so that positive, negative or minimal correlations (in time) are found between observed tides and the SPW (Baumgaertner et al, 2006;Xu et al, 2009a, c;Hibbins et al, 2010).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional work is necessary for a better understanding of the interhemispheric SPW-tidal coupling processes. This is the subject of scrutiny in another paper by the present authors (Xu et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Using the semidiurnal tide (SDT) data from meteor radars (MWR) at Eureka (801N, 861W), Svalbard (781N, 161E) and Collm (511N, 151E), and medium frequency radars (MFR) at Tromsø (701N, 191E) and Saskatoon (521N, 2531E), Xu et al (2009) discussed the relationships between the day-to-day variability of the SDT in the Northern Hemisphere (NH) mesosphere and stationary planetary wave (SPW) with zonal wavenumber S ¼ 1 (SPW1) in the Southern Hemisphere (SH) during NH summer-fall (July-October). Their results showed that the SDT amplitudes observed at Arctic latitudes (801N) usually do not provide persistent correlations with the SH SPW1 amplitudes.…”
Section: Introductionmentioning
confidence: 99%